The Management and Development of Productive Waqf at Syirkah Amanah Gas Station in Lumajang - Wibisono, Yusuf; Mudhofar, Muhammad (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Productive Waqf is the management of waqf donations from the community that are developed to generate a sustainable surplus that can improve the welfare of society. Waqf donations may take the form of movable assets, such as cash and precious metals, or immovable assets, such as land and buildings. This research focuses on the management and development of productive Waqf at Syirkah Amanah gas station in Lumajang, and on the distribution of dividends from the results of that management for the gas station's business in Lumajang. This study is a descriptive qualitative research. The primary data collected in this research come from the documents of the Annual General Meeting of Shareholders of Syirkah Amanah gas station, held annually, as well as from interviews and observations, and are supported by other secondary data. Based on internal data, the establishment of the Syirkah Amanah gas station on waqf assets utilized capital and community shares. During its development, the management of the productive Waqf for Syirkah Amanah gas station has experienced strong, dynamic growth, generating profits each year. As a result, Syirkah Amanah gas station can distribute dividends to its shareholders, based on the results of the General Meeting of Shareholders.